Support–Activity Relationship in Heterogeneous Catalysis for Biomass Valorization and Fine-Chemicals Production - Andrea Lazzarini (MDPI AG, 2021)
Heterogeneous catalysts are progressively expanding their field of application, from high-throughput reactions for traditional industrial chemistry with production volumes reaching millions of tons per year, a sector in which they are key players, to more niche applications for the production of fine chemicals. These novel applications require a progressive utilization reduction of fossil feedstocks, in favor of renewable ones. Biomasses are the most accessible source of organic precursors, having as advantage their low cost and even distribution across the globe. Unfortunately, they are intrinsically inhomogeneous in nature and their efficient exploitation requires novel catalysts. In this process, an accurate design of the active phase performing the reaction is important; nevertheless, we are often neglecting the importance of the support in guaranteeing stable performances and improving catalytic activity. This review has the goal of gathering and highlighting the cases in which the supports (either derived or not from biomass wastes) share the worth of performing the catalysis with the active phase, for those reactions involving the synthesis of fine chemicals starting from biomasses as feedstocks.